“Recursos didácticos para la enseñanza aprendizaje en el área de la Matemática en el subnivel de educación general básica elemental de la escuela “Joaquín Anda Viteri” - Caisaguano Bungacho, Mónica Gabriela (2022)
The didactic resources in the first years of Basic Education in the area of mathematics are important for those who begin to insert themselves in the educational field, their previously elaborated, planned use guarantees learning within the classroom, when the manipulation of different specific didactic resources, the possibility of forming schemes and establishing relationships of knowledge is difficult, which implies a failure in the abstraction of concepts, which the student will not be able to apply in solving everyday problems. Hence, the objective of this research work is to develop different didactic resources for the teaching and learning of mathematics with the students of the Elementary Sublevel of the “Joaquín Anda Viteri” School. The research has a qualitative and descriptive approach; For the collection of information, the interview technique and direct observation were used, through the application of instruments such as the question guide and the observation guide. The results evidenced the need to develop a proposal for specific didactic resources for learning mathematics, a proposal that was subjected to a process of theoretical validation by experts, which obtained an assessment in the excellent range. This research will help teachers promote student learning in the area of mathematics, according to the needs using easy-to-do teaching resources, to improve the teaching-learning process, especially the motivation and interest of the subjects immersed in the educational process.